Labor Market Concentration - José Azar; Ioana E. Marinescu; Marshall Steinbaum (Institute of Labor Economics (IZA), 2017)
A product market is concentrated when a few firms dominate the market. Similarly, a labor market is concentrated when a few firms dominate hiring in the market. Using data from the leading employment website CareerBuilder.com, we calculate labor market concentration for over 8,000 geographic-occupational labor markets in the US. Based on the DOJ-FTC horizontal merger guidelines, the average market is highly concentrated. Using a panel IV regression, we show that going from the 25th percentile to the 75th percentile in concentration is associated with a 17% decline in posted wages, suggesting that concentration increases labor market power.
Keywords: J30; J42; L40; 330; monopsony; oligopsony; labor markets; competition policy